Exploring a Rare Association: Systematic Review of Hypercalcemia in Nontuberculous Mycobacterial Infections - Ramon Cohen; Viviana Ostrovsky; Lior Zornitzki; Daniel Elbirt; Taiba Zornitzki (Microorganisms)
Hypercalcemia represents a rare complication of nontuberculous Mycobacterium (NTM) infections, particularly in individuals with human immunodeficiency virus (HIV) positivity. This systematic review examines NTM infections associated with hypercalcemia, including the presentation of a novel and illustrative case of Mycobacterium simiae. A meticulous literature search identified 24 cases relevant to this phenomenon (11 HIV-positive and 13 non-HIV), which were included in the analysis. Key clinical and laboratory findings reveal significant contrasts between HIV-positive and non-HIV patients. In the HIV-positive cohort, hypercalcemia is commonly developed after the initiation of highly active antiretroviral therapy (HAART) or treatment for NTM infections despite severe underlying immunosuppression. Conversely, in the non-HIV group, a spectrum of immunosuppressive conditions, including chronic renal failure and prolonged use of immunosuppressive drugs, was implicated in the pathogenesis of NTM infections with hypercalcemia. Two distinct mechanistic pathways likely underlie this association. In HIV-positive patients, immune restoration following HAART appears to drive granuloma formation and excessive 1,25-dihydroxyvitamin D production. In non-HIV individuals, prolonged immune suppression may facilitate macrophage activation associated with NTM infections, thereby contributing to hypercalcemia. Treatment strategies varied and included bisphosphonates, corticosteroids, and hemodialysis. Notably, bisphosphonates emerged as a safe and effective option in most cases. Antibiotic therapy was deemed unnecessary when hypercalcemia was the sole symptom of NTM infection. This review underscores the importance of recognizing hypercalcemia as a potential complication of NTM infections and tailoring management strategies to the patient’s underlying immunological status.